VALVE INDUCTION GENERATORS OF RADIAL EXCITATION WITH COMBINED WINDINGS - V.D. Lushchik (National Technical University "Kharkiv Polytechnic Institute", 2014)
The design and principle of operation of inductor generators with combined windings are described. The theoretical substantiation of advantages of considered generators is presented. The data of experimental investigations of generators with combined windings and, for comparison, generators, which are made in series are presented.